2019
DOI: 10.1590/1516-4446-2018-0041
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of parenting styles and parental drunkenness to adolescent drinking

Abstract: Objective:To estimate the association of parental drunkenness and parenting style with alcohol consumption among adolescents and the contributions of parental drunkenness and parenting style to the prevalence of binge drinking among adolescents.Method:Cross-sectional survey of a representative sample of secondary students aged 13 to 18 from 27 Brazilian state capitals (n=17,028). Private and public schools were included. A self-report questionnaire collected data on adolescents’ alcohol drinking behavior, pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
1
18
0
7
Order By: Relevance
“…Similar to previous studies, we established in the Nepalese context that authoritarian parenting is a risk factor for suicidal behavior. In support of our findings, studies on parenting and adolescent outcome have stated that parenting with high control and harsh parenting, i.e., the authoritarian parenting style, lead to negative outcomes in their adolescent children, such as depression, diminished academic success, and self-harm, while authoritative parenting has a beneficial effect [41,[43][44][45][46][47][48][49][50][51][52]61,83,88]. Hence, our findings suggested that parents can prevent suicidal behavior in their adolescent children by reducing their authoritarian parenting style.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar to previous studies, we established in the Nepalese context that authoritarian parenting is a risk factor for suicidal behavior. In support of our findings, studies on parenting and adolescent outcome have stated that parenting with high control and harsh parenting, i.e., the authoritarian parenting style, lead to negative outcomes in their adolescent children, such as depression, diminished academic success, and self-harm, while authoritative parenting has a beneficial effect [41,[43][44][45][46][47][48][49][50][51][52]61,83,88]. Hence, our findings suggested that parents can prevent suicidal behavior in their adolescent children by reducing their authoritarian parenting style.…”
Section: Discussionsupporting
confidence: 85%
“…The range of total scores on the sections of the four-item authoritarian parenting, five-item authoritative parenting, and four-item indulgent parenting was 4–20, 5–25 and 4–20, respectively. We had developed the questionnaire items regarding the parent’s knowledge about the development of self-esteem in adolescents based on the following literatures: [ 1 , 2 , 3 , 4 , 7 , 11 , 30 , 31 , 68 ]; we had developed the items on parenting practice related to self-esteem based on the following literatures: [ 7 , 11 , 33 , 36 , 56 , 68 , 69 , 70 , 71 , 72 , 73 ]; and we had developed the items on parenting style based on the following literatures: [ 39 , 40 , 42 , 43 , 44 , 45 , 47 , 48 , 49 , 50 , 56 , 60 , 74 , 75 , 76 ]. The tool was developed in Nepali.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously showed, parental behavior is a major factor of value transfer and more effective than the words [30] and family members, especially mothers, are role models for adolescents [36]. In one study, 60 percent of alcoholic adolescents had alcoholic parents [40]. Higher hopefulness, self-esteem, and self-regulation, and reduced risky behaviors are some of the consequences of having a positive role model [37].…”
Section: Discussionmentioning
confidence: 98%
“…Three Brazilian surveys have related parenting styles to teenage alcoholism (Paiva et al, 2012;Valente et al, 2017;Zuquetto et al, 2019), employing self-report instruments to report parenting practices and alcohol use. The participants reported the number of doses of alcohol they normally ingested on a single occasion, which served as the criterion for forming groups of frequent, moderate or occasional drinkers.…”
Section: Called Attention To the Association Between Deficient Paternmentioning
confidence: 99%